Quality of Online Transportation Services for Women in Manado City, North Sulawesi Province - Pangemanan, Sofia E.; Sambiran, Sarah; Londa, Jeffry W.; Londa , Very Y. (Journal La Bisecoman, 2024)
Complaints about the quality of service can be seen from the punctuality, professionalism of the driver, cleanliness of the driver and facilities to the amount of service prices, safety and comfort. To make this online transportation service remain good and become the choice of the community, it is necessary to improve the service by improving the quality of service. This study was conducted to identify and analyze the quality of online transportation services specifically for women in Manado City. By conducting this study, it is hoped that there will be a recommendation that can be put forward regarding transportation problems in Manado City in terms of service quality for women. Therefore, this study was conducted using a qualitative design through a phenomenological approach. The research informants were women (office workers, students and housewives) users of online transportation services) and online transportation drivers. Data were collected through interviews with informants, conducting observations using online transportation and conducting secondary data document searches with the help of the Google Scholar application. The analysis technique was carried out by means of data reduction, data presentation and drawing conclusions and data verification. The research findings that online transportation is very much needed by the community to support smooth activities. Friendliness, competence, security, facilities and prices are important factors in the quality of online transportation services. Security is the most important factor for women in Manado City in choosing and using online transportation.